2015
DOI: 10.1001/jamaoncol.2015.1313
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing of Metastatic Cancer and Biomarkers of Treatment Response

Abstract: Importance Understanding molecular mechanisms of response and resistance to anticancer therapies requires prospective patient follow-up and clinical and functional validation of both common and low-frequency mutations. We describe a whole-exome sequencing (WES) precision medicine trial focused on patients with advanced cancer. Objective To understand how WES data affect therapeutic decision making in patients with advanced cancer and to identify novel biomarkers of response. Design, Setting, and Patients P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
280
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(287 citation statements)
references
References 12 publications
3
280
0
3
Order By: Relevance
“…For example, a number of studies using whole-exome sequencing to provide diagnoses for undiagnosed, suspected genetic conditions, resulted in a roughly 25% success rate, with a significant proportion of these successes resulting in the identification of mutations that had not been previously characterized 40 . In "N of 1" cancer cases for both retrospective 41 and prospective studies 42 , finding actionable mutations that can affect treatment choices happens in well over 50% of the cases, with a high percentage of the actionable mutations identified as being de novo. We anticipate that future searches for individuals resilient to various genetic defects will be most effective when combining the traditional searches for positive outliers in known extended families with very broad searches for positive outliers in the general population.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…For example, a number of studies using whole-exome sequencing to provide diagnoses for undiagnosed, suspected genetic conditions, resulted in a roughly 25% success rate, with a significant proportion of these successes resulting in the identification of mutations that had not been previously characterized 40 . In "N of 1" cancer cases for both retrospective 41 and prospective studies 42 , finding actionable mutations that can affect treatment choices happens in well over 50% of the cases, with a high percentage of the actionable mutations identified as being de novo. We anticipate that future searches for individuals resilient to various genetic defects will be most effective when combining the traditional searches for positive outliers in known extended families with very broad searches for positive outliers in the general population.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Massively parallel sequencing (MPS) offers several advantages over the single-gene approach (10)(11)(12)(13)(14)(15); most importantly, it offers a more sensitive and more comprehensive genomic profile that does not apply an a priori knowledge of alterations that may be more common in a specific tumor type. Several academic centers have demonstrated that large MPS panels can be employed in practice (11,16,17), with a number of groups reporting a high rate of "actionable" (informative or clinically relevant) gene alterations in clinical cancer cohorts (4,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have shown that only a small proportion of patients (~5%-10%) have their cancer genomic data used as a criterion for selection of a targeted therapy or a clinical trial (16,19,20). A variety of logistic, operational, and medical reasons (20) have been cited, such as identification of the appropriate genomic target at the right time in a patient's clinical course, time to result, the value of biopsy at the time of progressive disease (21), choice of conventional treatment protocols, access to clinical trials (16,20) or off-label use of drug (19), and patient preferences (20). Similarly, evaluation of the confidence of physicians at our institutions in using genomic data to make decisions on patient treatment options (22) indicates that not all "actionable" genomic data will be acted upon.…”
Section: Introductionmentioning
confidence: 99%
“…[8,11,12] For mutations without reported annotation and for variants of unknown significance, interpretation included individual review of the published literature and cancer genome databases, including canSAR, [14] cBioPortal for Cancer Genomics, [15,16] and Tumor Portal. [17] Novel missense gene mutations were modeled using structure-homology modeling with SWISS-MODEL.…”
Section: Pediatric Molecular Tumor Boardmentioning
confidence: 99%